Pemikiran Politik Abdurrahman Wahid dan Pengaruhnya Terhadap Politik Partai Kebangkitan Bangsa - Canra Purnama; M. Ied Al-Munir; Muh. Rusydy; Aprizal Wahyudi Diprata (Dinasti Review Publisher, 2023)
This research aims to answer the following problems: (1) Abdurrahman Wahid's political thought concept. (2) PKB Political Thought. (3) The influence of Abdurrahman Wahid's political thoughts on PKB political policies. The type of research is qualitative with a research approach, namely a sociological and political approach. The data collection methods used were observation, interviews, and documentation. Data processing and analysis techniques were carried out in three stages, namely: data reduction, data presentation and conclusions. The results of this research show the concept of Abdurrahman Wahid's thinking referring to the teachings of Indonesian Islamic values ??which are framed in Pancasila and the Constitution. Abdurrahman Wahid's thoughts became the PKB's political vision regarding the state, nationalism, pluralism, which can be seen through the PKB's policies in Jambi which refer to Abdurrahman Wahid's thoughts. The state is present to provide facilities to the community. Carrying out interfaith dialogue activities, sharing basic necessities in joint mourning activities as a reflection of a sense of nationalism and humanism. Assistance activities for the community to obtain religious freedom according to their beliefs as an attitude of pluralism. The implications of this research answer the need for an indication of Abdurrahman Wahid's thoughts in the Jambi PKB Party as an excellent concept of thought to implement for the progress of the nation and state. One example is the birth of study groups with the names Gemasaba, Lakumham and Garda Bangsa.